The Early Detection of LPG Gas Cylinder Leaks in Households Based on the Internet of Things with SMS Message Notifications - Budi Wibowo; Andrie Yuswanto (Sultan Publisher, 2023)
Almost all residences, places of business, and restaurants use LPG gas cylinders for daily cooking. We can see nowadays the many problems caused by these gas cylinders, one of which is a fire caused by a leak in the gas cylinder. Therefore we need an appropriate technology to overcome this problem, namely a tool to detect gas leaks using sensors and provide notifications to owners to reduce the impact of fires caused by gas leaks so that people can be safe. In this study, the microcontroller was ATMega 328 Arduino Uno, sim 900a, to provide danger notifications in the form of SMS and MQ-2 gas sensors (LPG, Natural Gas, Coal Gas) with an LPG gas leak detector with hazard notifications via SMS on the impact of a fire. Caused by a gas leak can be detected early so that a fire does not occur in the household.